2014
DOI: 10.1002/jcp.24781
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate Induces ER Stress and Autophagy in H9c2 Cells: Implications for Apoptosis and Adiponectin Resistance

Abstract: The association between obesity and heart failure is well documented and recent studies have indicated that understanding the physiological role of autophagy will be of great significance. Cardiomyocyte apoptosis is one component of cardiac remodeling which leads to heart failure and in this study we used palmitate-treated H9c2 cells as an in vitro model of lipotoxicity to investigate the role of autophagy in cell death. Temporal analysis revealed that palmitate (100 μM) treatment induced a gradual increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 55 publications
3
51
1
Order By: Relevance
“…Although Wei et al reported that U0126, an inhibitor of extracellular signal-regulated kinase (ERK), reduced PA-induced apoptosis through partial suppression of intracellular ROS generation, there was no direct evidence to prove the involvement of ROS [4]. A recent study demonstrated that autophagy was induced by PA as an adaptive response to ER stress since it was sensitive to ER stress inhibition in H9c2 cells [9], however, whether ROS plays a role in PA-induced autophagy and apoptosis remains unknown.…”
Section: Introductionmentioning
confidence: 95%
“…Although Wei et al reported that U0126, an inhibitor of extracellular signal-regulated kinase (ERK), reduced PA-induced apoptosis through partial suppression of intracellular ROS generation, there was no direct evidence to prove the involvement of ROS [4]. A recent study demonstrated that autophagy was induced by PA as an adaptive response to ER stress since it was sensitive to ER stress inhibition in H9c2 cells [9], however, whether ROS plays a role in PA-induced autophagy and apoptosis remains unknown.…”
Section: Introductionmentioning
confidence: 95%
“…Is AMPK/mTOR-dependent or -independent, RespectivelyRecent studies have shown that the cytotoxic effects of fatty acids and nutrient starvation can induce autophagy (51)(52)(53)(54). However, it is not known whether the two different stresses induce autophagy in the same manner.…”
Section: Autophagy Induced By Nutrient Starvation or Lipotoxicitymentioning
confidence: 99%
“…Our data indicate that at least two of the three major UPR signaling pathways, IRE1/XBP1 and PERK/CHOP were altered by PA. It has been suggested that ER stress is involved in PA-induced apoptosis [12,19,20,31]. Based on the data that blocking ER stress inhibited PA-induced apoptosis in SMMC-7721 cells, we suggest that ER stress promotes PA-induced apoptosis in hepatocyte.…”
Section: Discussionmentioning
confidence: 65%
“…It has been reported that PA can initiate ER stress response in various cell types [29][30][31][32]. We firstly detected the potential role of PA in the induction of ER stress in SMMC-7721 cells.…”
Section: Discussionmentioning
confidence: 98%